Pengaruh Live Streaming, Diskon, Dan Harga Terhadap Keputusan Pembelian Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pada Tiktok Shop Generasi Z Di Situbondo Kota - Elok Laras N; Yuniorita Indah Handayani; Hayatul Maspufah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study is entitled "Live Streaming, Discounts, and Prices on Purchasing Decisions through Customer Satisfaction as an Intervening Variable in Generation Z TikTok Shop in Situbondo City". This study aims to determine the direct and indirect effects of live streaming, discounts, and prices on purchasing decisions and their influence on customer satisfaction as an intervening variable. The population in this study was 50 Gen Z respondents. This type of research uses quantitative research methods. The sampling technique used is purposive sampling. The data analysis method uses path analysis with the help of SPSS 25. The tests used are instrument tests (validity tests and reliability tests), classical assumption tests (normality tests, heteroscedasticity tests, multicollinearity tests), hypothesis tests (t tests), and Sobel tests. The results of the analysis show that live streaming does not affect customer satisfaction, discounts and prices affect customer satisfaction. Furthermore, live streaming, discounts, and prices do not affect purchasing decisions, customer satisfaction does affect purchasing decisions. Then, live streaming and discounts do not affect purchasing decisions through customer satisfaction, and prices affect purchasing decisions through customer satisfaction..